Analysis of process-induced deformations and residual stresses in curved composite parts considering transverse shear stress and thickness stretching. (1st June 2020) - Zappino, E.; Zobeiry, N.; Petrolo, M.; Vaziri, R.; Carrera, E.; Poursartip, A.
Abstract: A computationally efficient modeling approach for the accurate evaluation of process-induced deformations and residual stresses in composite parts is presented. A family of refined one-dimensional kinematic models, developed in the framework of the Carrera Unified Formulation, has been used to predict the accurate through-thickness deformation of layered structures during the manufacturing process. The composite material curing phase has been simulated exploiting the capabilities of the software RAVEN. A cure hardening instantaneously linear elastic model has been used. A benchmark based on an L-shaped component has been selected to compare the results obtained using different computational approaches. A closed-form solution, the present refined one-dimensional models and classical solid models, have been considered. The effects of the modeling approach on the prediction of the spring-in angle and on the residual stress field have been evaluated and discussed. The results demonstrate that the use of refined kinematic models can lead to a high-fidelity description of the problem and a quasi-3D accuracy while reducing the computational cost with respect to classical FEM approaches. The through-thickness effects have been predicted with a high level of accuracy and the use of layer-wise models has led to an accurate description of the stress field, including the transverse shear stresses.